Dyskeratosis congenita - Lorenzo Gitto; Robert Stoppacher; Timothy Eric Richardson; Serenella Serinelli (University of São Paulo, 2021)
Dyskeratosis congenita (DC) is a genetic syndrome with progressive multisystem involvement classically characterized by the clinical triad of oral leukoplakia, nail dystrophy, and reticular hyperpigmentation. Frequent complications are bone marrow failure, increased rate of malignancy, lung and liver diseases. DC results from an anomalous progressive shortening of telomeres resulting in DNA replication problems inducing replicative senescence. We report a death due to DC in a 16-year-old male with bone marrow failure and multiple organ dysfunction. At autopsy, nail dystrophy and skin hypopigmentation were observed. Gross and microscopic examinations of the internal organs showed cardiac hypertrophy, multiple lung consolidations and prominent interstitial fibrosis, liver cirrhosis, and fibrosis. Multiple foci of extramedullary hematopoiesis were identified, including on the epidural surface of the dura, that is an infrequent location, mimicking a focal area of epidural hemorrhage. Only a few autopsy studies about DC are reported in the literature. Further research should be done to understand the pathophysiology of the disease and its complications.